A behavioural dynamic model of the relative age effect - Pierson, K.; Addona, V.; Yates, P. (Journal of Sports Sciences, 2014)
The relationship between date of birth and success in a variety of sports, including hockey, is well established. This phenomenon is known as the relative age effect (RAE). We model the RAE in Canadian youth hockey as a positive feedback loop where an initial age advantage is reinforced through additional training and playing opportunities based on perceived skill superiority. The same causal mechanism leads to a higher quit rate for relatively younger players. Our model effectively replicates the birth month distribution of Canadian National Hockey League players (R2 = 86.79%) when driven by Canadian birth distributions. We use this model to evaluate three policies that aim to lessen the RAE. All of the policies reduce the RAE with a significant delay. The most effective policy is a combination of providing additional support to age disadvantaged children and rotating the cut-off date for youth leagues between January 1st and July 1st annually. In equilibrium, this approach leads to a 96% reduction in the RAE compared to the base case.